ANALYSIS OF STRUCTURAL-SEMANTIC AND COMMUNICATIVE-PRAGMATIC FEATURES OF LEXICAL MEANS REPRESENTING THE CATEGORY OF INTENTIONALITY IN THE ENGLISH AND UZBEK LANGUAGES - NajmeddinovAhmad Rahmatovich (Лучшие интеллектуальные исследования, 2024)
Intentionality as one of the main aspects of the speech mechanism is one of the priority areas of research in modern linguistics. The study of the intellectual needs of communicants and the question of its manifestation in speech arose as an object of study of the theory of speech acts. As a result of this study, it became clear that the degree of intentionality and its implementation in speech with the help of linguistic means depends on the linguistic and verbal competence of the speaker / author, the methods and principles of conveying the intended goal in the context.